A high-tenacity polyester composition and a method for making the same

CN119144127BActive Publication Date: 2026-10-09CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310718858.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-16
Publication Date
2026-10-09
Estimated Expiration
2043-06-16

AI Technical Summary

Technical Problem

[0008]本发明采用创新共混工艺,解决增韧剂在基体中相容性差、分散不佳的难题,并大幅降低增韧剂用量,实现增韧剂在基体中合理分布与分散,获得了一种高韧性聚酯组合物,由该组合物制备的产品韧性优良,同时材料还具有足够的强度

Benefits of technology

[0039] This invention employs an innovative blending process to prepare a high-toughness polyester composition, improving the dispersion of toughening agents in the matrix and enhancing the compatibility between the matrix and the toughening agent. Unexpectedly, even with a reduction of over 50% in the amount of toughening agent, the polyester composition still maintains excellent toughness and sufficient strength. Compared to conventional PETG, the impact strength of this polyester composition is increased by more than four times without affecting tensile strength, solving the problems of poor compatibility and dispersion of toughening agents in the matrix. This results in a high-toughness, high-strength polyester composition with excellent toughness and sufficient strength. This expands the application fields and usage areas of polyester materials and has significant market potential.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a high-toughness polyester composition and a preparation method thereof, and belongs to the polyester field. The preparation method of the polyester is that a part of polyester is melt-blended with an additive I to obtain a blend A, the blend A is melt-blended with a toughening agent to obtain a blend B, the remaining part of the polyester, an additive II and the blend B are melt-blended, and finally the mixture is extruded and cut into particles or is made into other suitable shapes. The application adopts an innovative blending process to prepare a high-toughness polyester composition, improves the dispersibility of the toughening agent in the matrix, and improves the compatibility of the matrix and the toughening agent. Meanwhile, it is accidentally found that even if the amount of the toughening agent is reduced by more than 50%, the polyester composition still maintains excellent toughness and sufficient strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyester, and more specifically to a high-toughness polyester material, and also to articles made from said polyester composition. Background Technology

[0002] Polyethylene terephthalate-1,4-cyclohexanediethanol (PETG) is a copolyester material obtained by transesterification and polycondensation of terephthalic acid (PTA), ethylene glycol (EG), and 1,4-cyclohexanediethanol (CHDM). PETG possesses excellent transparency, chemical resistance, and stress whitening resistance, and can be rapidly thermoformed or extruded and blow-molded. It is widely used in sheets, plastic sheets, and cosmetic packaging.

[0003] Household products are facing increasingly stringent material requirements, necessitating the toughening of PETG. Currently, a common toughening method is the addition of toughening agents. However, this method often leads to problems such as poor component compatibility and poor dispersion. Therefore, to economically and rationally improve the toughness of PETG materials, a new PETG composition and its preparation method are needed.

[0004] Chinese patent CN102816414B discloses a high heat-resistant and flame-retardant reinforced PET composition and its preparation method, which improves the notched impact strength of the PET composition by adding a reactive toughening agent. The PET composition includes: PET, reactive toughening agent, nucleating agent masterbatch, brominated flame retardant, inorganic flame retardant, reinforcing agent, chain extender, lubricant, and antioxidant. The composition is prepared by twin-screw blending.

[0005] Patent CN105524433A discloses a method for preparing high-toughness PET. This method involves adding an appropriate amount of branched polystyrene (BPS) and liquid paraffin to a PET matrix, followed by melt blending to obtain a PET / BPS blend. While the preparation method is simple, the toughening agent has poor dispersibility; furthermore, the addition of the compatibilizer liquid paraffin can affect the properties of the blend.

[0006] Chinese patent CN112341781A discloses a high elongation spray-coated PC / PBT alloy material and its preparation method. It employs reactive toughening agents and core-shell structured organosilicon-based toughening agents to achieve compatibilization and toughening of the PC / PBT alloy. The alloy contains approximately 50% PC by mass, resulting in high manufacturing costs.

[0007] Chinese patent CN103131138B discloses a thermoplastic polyester composition and its preparation method, which improves the toughness of the thermoplastic polyester composition by using a blending toughening agent. The toughening agent includes a reclaimed rubber toughening agent or an impact resin toughening agent. Summary of the Invention

[0008] This invention employs an innovative blending process to solve the problems of poor compatibility and dispersion of toughening agents in the matrix, and significantly reduces the amount of toughening agent used. This achieves a reasonable distribution and dispersion of the toughening agent in the matrix, resulting in a high-toughness polyester composition. Products prepared from this composition exhibit excellent toughness, while also possessing sufficient strength.

[0009] The objective of this invention can be achieved through the following technical solutions:

[0010] A method for preparing a high-toughness polyester composition, the method comprising the following steps:

[0011] (1) A portion of polyester is melt-blended with additive I to obtain blend A;

[0012] Additive I is selected from water, diols, diacids, terephthalate polymers, antioxidants, heat stabilizers, branching agents, colorants, release agents, flame retardants, and any combination thereof;

[0013] (2) Blend A can be obtained by melt blending the blend A with the toughening agent;

[0014] (3) The remaining polyester, additive II and blend B are melt-blended, and the mixture is finally extruded into pellets or made into other suitable shapes.

[0015] Additive II is selected from chain extenders, colorants, release agents, antioxidants, flame retardants, and any combination thereof.

[0016] In the technical solution of the present invention: the additive I mentioned in step (1) is selected from water and antioxidant, or the additive I is selected from diol and terephthalate polymer, or the additive I is selected from diol, terephthalate polymer and heat stabilizer.

[0017] The polyester is selected from polyethylene terephthalate 1,4-cyclohexanediol ester;

[0018] In some preferred technical solutions: the additive I mentioned in step (1) is selected from water and antioxidant in a mass ratio of 1:20 to 40, or the additive I is selected from terephthalic acid ester polymer, diol and heat stabilizer in a mass ratio of 70 to 90:1:5 to 10; or the additive I is selected from diol and heat stabilizer in a mass ratio of 1:5 to 10.

[0019] In the technical solution of the present invention: the intrinsic viscosity of the blend A in step (1) is 0.57-0.67 dL / g, the total amount of terminal carboxyl groups and terminal hydroxyl groups is 120-180 mol / t, and the molar ratio of terminal carboxyl groups and terminal hydroxyl groups is 1:6-1:2.

[0020] In the technical solution of the present invention: at least one toughening agent in step (2) is selected from functionalized maleic anhydride toughening agent, glycidyl methacrylate toughening agent, and styrene block toughening agent.

[0021] In some preferred technical solutions: the toughening agent is KRATON FG1924 or AX8900.

[0022] In the technical solution of this invention: the weight parts of polyester, additive I, toughening agent and additive II are 75-95 parts, 0.1-5 parts, 5-20 parts and 0.1-2 parts respectively;

[0023] In the technical solution of this invention, a portion of the polyester comprises 5-30 wt% of the total polyester content. More preferably, a portion of the polyester comprises 5-20 wt% of the total polyester content.

[0024] In the technical solution of this invention: the blend A is in a solid or molten state, and the preferred blend A is in a molten state.

[0025] In the technical solution of this invention: the diol mentioned in step (1) is selected from at least one of ethylene glycol, propylene glycol, butanediol, hexanediol, 1,4-cyclohexanediethanol, isosorbide and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; preferably: the diol is 1,4-cyclohexanediethanol;

[0026] The dicarboxylic acid mentioned in step (1) includes at least one selected from oxalic acid, malonic acid, succinic acid, adipic acid and 1,4-cyclohexanedicarboxylic acid;

[0027] The terephthalate polymer mentioned in step (1) is selected from at least one of PBT, PBA, PBST and PBAT;

[0028] The antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076 and antioxidant 1222;

[0029] The heat stabilizer is selected from at least one of trimethyl phosphate (TMP), triethyl phosphate (TEP), triethyl phosphate (TEPA), and triphenyl phosphate (TPP).

[0030] In the technical solution of this invention: melt blending uses a melt mixer selected from a single-screw or twin-screw extruder, a mixer, a kneader, an internal mixer, and an injection molding machine;

[0031] The temperature of the melt mixer is between 180 and 260°C, preferably between 200 and 250°C.

[0032] In the technical solution of this invention: Additive II is antioxidant 1222 or antioxidant 1010.

[0033] A high-toughness polyester composition, which is prepared by the above-described method.

[0034] In the technical solution of this invention: the high-toughness polyester composition obtained by the above method is used in cosmetic packaging, food utensils, household goods, medical devices, machinery and equipment, indoor and outdoor signs, and furniture and building materials.

[0035] In the technical solution of this invention, the condition for melt blending is to feed the material into a twin-screw extruder so that the material is fully melt-blended and uniformly mixed. The operating temperature of the twin-screw extruder is 200℃-260℃.

[0036] In the technical solution of this invention, the amount of toughening agent is greatly reduced, the composition matrix can maintain strong intermolecular chain forces, and the polyester composition can be ensured to have sufficient tensile strength.

[0037] The technical solution of this invention includes: a high-toughness polyester composition, wherein the tensile strength is 40-46 MPa, the flexural strength is 60-62 MPa, and the impact strength is 20-52 kJ / m. 2 .

[0038] The beneficial effects of this invention are:

[0039] This invention employs an innovative blending process to prepare a high-toughness polyester composition, improving the dispersion of toughening agents in the matrix and enhancing the compatibility between the matrix and the toughening agent. Unexpectedly, even with a reduction of over 50% in the amount of toughening agent, the polyester composition still maintains excellent toughness and sufficient strength. Compared to conventional PETG, the impact strength of this polyester composition is increased by more than four times without affecting tensile strength, solving the problems of poor compatibility and dispersion of toughening agents in the matrix. This results in a high-toughness, high-strength polyester composition with excellent toughness and sufficient strength. This expands the application fields and usage areas of polyester materials and has significant market potential. Detailed Implementation

[0040] The present invention will be further described below with reference to embodiments, but the scope of protection of the present invention is not limited thereto:

[0041] Test method:

[0042] Tensile properties were tested according to GB / T1040.2-2006. Notched impact strength of simply supported beams was tested according to GB / T1043-2008.

[0043] Comparative Example 1:

[0044] PETG was selected from SK Chemicals' SKYGREEN K2012. 89 parts PETG, 10 parts KRATON FG1924, and 1 part antioxidant 1010 were placed in a high-speed mixer and premixed at 500 rpm for 5 minutes. The premix was then fed to a twin-screw melt extruder for pelletizing, and standard test specimens were prepared using an injection molding machine. The melt temperature for both extrusion and injection molding was maintained within the range of 200–250°C.

[0045] Comparative Example 2:

[0046] PETG was selected from SK Chemicals' SKYGREEN K2012. 79 parts PETG, 20 parts KRATON FG1924, and 1 part antioxidant 1010 were placed in a high-speed mixer and premixed at 500 rpm for 5 minutes. The premix was then fed to a twin-screw melt extruder for pelletizing, and standard test specimens were prepared using an injection molding machine. The melt temperature for both extrusion and injection molding was maintained within the range of 200–250°C.

[0047] Example 1:

[0048] PETG was selected from SK Chemicals' SKYGREEN K2012.

[0049] Step (1): Add 5 parts PETG, 0.005 parts water, and 0.2 parts antioxidant 1010 to a high-speed mixer and stir at 500 r / min for 5 min. Then, use an extruder to melt-blend the mixture to obtain blend A with an intrinsic viscosity of 0.58 dL / g. Wherein: the high-speed mixer is added to the feed port of a single-screw extruder, and the temperatures of zones one, two, three, and four of the single-screw barrel are set to 220℃, 230℃, 240℃, and 240℃ respectively.

[0050] Step (2): Melt-state A and 10 parts of KRATON FG1924 are melt-blended in a twin-screw side-feed extruder to obtain blend B. The melt-blending conditions are as follows: the twin-screw side-feed extruder is selected, KRATON FG1924 is added at the first feed port, and molten state A is conveyed to the extruder from the melt section feed port. The temperatures of zones one to ten of the twin-screw barrel are set to 210℃, 215℃, 220℃, 225℃, 230℃, 235℃, 240℃, 240℃, 240℃, and 245℃ respectively.

[0051] Step (3): 84 parts PETG and 0.8 parts antioxidant 1010 were added to the first feed port of the twin-screw extruder. Blend B was then fed to the second feed port of the twin-screw extruder using a side feeder. The material was then extruded and pelletized. Standard test specimens were prepared using an injection molding machine. The melt temperature during both the blending extrusion and injection molding processes was maintained within the range of 200–250°C.

[0052] Example 2:

[0053] PETG was selected from SK Chemicals' SKYGREEN K2012.

[0054] Step (1): Add 10 parts PETG, 0.005 parts water, and 0.2 parts antioxidant 1010 to a high-speed mixer and stir at 500 r / min for 5 min. Then, use an extruder to melt-blend the mixture to obtain blend A with an intrinsic viscosity of 0.63 dL / g. Wherein: the high-speed mixer is added to the feed port of a single-screw extruder, and the temperatures of zones one, two, three, and four of the single-screw barrel are set to 220℃, 230℃, 240℃, and 240℃ respectively.

[0055] Step (2): Melt-state A and 10 parts of KRATON FG1924 are melt-blended in a twin-screw side-feed extruder to obtain blend B. The melt-blending conditions are as follows: a twin-screw extruder is selected as the twin-screw side-feed extruder; KRATON FG1924 is added at the first feed port; and molten state A is conveyed to the extruder from the melt section feed port. The temperatures of zones one to ten of the twin-screw barrel are set to 210℃, 215℃, 220℃, 225℃, 230℃, 235℃, 240℃, 240℃, 240℃, and 245℃, respectively.

[0056] Step (3): 74 parts PETG and 0.8 parts antioxidant 1010 were added to the first feed port of the twin-screw extruder. Blend B was then fed to the second feed port of the twin-screw extruder using a side feeder. The material was then extruded and pelletized. Standard test specimens were prepared using an injection molding machine. The melt temperature during both the blending extrusion and injection molding processes was maintained within the range of 200–250°C.

[0057] Example 3:

[0058] PETG was selected from SK Chemicals' SKYGREEN K2012.

[0059] Step (1): Add 15 parts PETG, 0.007 parts water, and 0.2 parts antioxidant 1010 to a high-speed mixer and stir at 500 r / min for 5 min. Then, use an extruder to melt-blend the mixture to obtain blend A with an intrinsic viscosity of 0.66 dL / g. Wherein: the high-speed mixer is added to the feed port of a single-screw extruder, and the temperatures of zones one, two, three, and four of the single-screw barrel are set to 220℃, 230℃, 240℃, and 240℃ respectively.

[0060] Step (2): Melt-state A and 10 parts of KRATON FG1924 are melt-blended in a twin-screw side-feed extruder to obtain blend B. The melt-blending conditions are as follows: a twin-screw extruder is selected as the twin-screw side-feed extruder; KRATON FG1924 is added at the first feed port; and molten state A is conveyed to the extruder from the melt section feed port. The temperatures of zones one to ten of the twin-screw barrel are set to 210℃, 215℃, 220℃, 225℃, 230℃, 235℃, 240℃, 240℃, 240℃, and 245℃, respectively.

[0061] Step (3): 64 parts PETG and 0.8 parts antioxidant 1010 were added to the first feed port of the twin-screw extruder. Blend B was then fed to the second feed port of the twin-screw extruder using a side feeder. The material was then extruded and pelletized. Standard test specimens were prepared using an injection molding machine. The melt temperature during both the blending extrusion and injection molding processes was maintained within the range of 200–250°C.

[0062] Table 1 shows the test results of various material properties in Comparative Examples 1-2 and Examples 1-3:

[0063] A-terminal carboxyl group of the mixture (mol / t) / / 45 35 38 Hydroxyl group at terminal A of the mixture (mol / t) / / 134 89 83 Viscosity of mixture A (dL / g) / / 0.58 0.63 0.66 Mixture A (raw material, fraction) 0 0 5 10 15 Toughening agent (parts) 10 20 10 10 10 Tensile strength (MPa) 45.9 35.3 45.8 45.2 44.7 Bending strength (MPa) 56.3 45.2 60.5 60.5 61.8 <![CDATA[Impact strength (kJ / m 2 )]]> 12.6 30.8 25.1 45.5 49.8

[0064] The above provides a detailed description of a high-toughness polyester composition and its preparation method provided by the present invention. As can be seen from Examples 1-3, the toughness of the high-toughness polyester composition increases with the increase of the mass fraction of blend A, with Example 3 exhibiting the best toughness. Compared with Comparative Example 1 using a conventional process, Example 3 shows a nearly four-fold increase in impact strength, while maintaining comparable tensile strength and slightly higher flexural strength. Compared with Comparative Example 2 with a high amount of toughening agent, Example 3 demonstrates a significant advantage in mechanical strength, while also increasing impact strength by 62%.

[0065] Comparative Example 3:

[0066] Eastman's Eastar GN078 was used for PETG. 92 parts PETG, 7 parts LOTADER AX8900, and 1 part antioxidant 1222 were placed in a high-speed mixer and premixed at 500 rpm for 5 minutes. The premix was then fed to a twin-screw melt extruder for pelletizing, and test specimens were injection molded using an injection molding machine. The melt temperature for both extrusion and injection molding was maintained within the range of 200–250°C.

[0067] Comparative Example 4:

[0068] Eastman's Eastar GN078 was used for PETG. 84 parts PETG, 15 parts LOTADER AX8900, and 1 part antioxidant 1222 were placed in a high-speed mixer and premixed at 500 rpm for 5 minutes. The premix was then fed to a twin-screw melt extruder for pelletizing, and finally injection molded into test specimens. The melt temperature for both extrusion and injection molding was maintained within the range of 200–250°C.

[0069] Example 4:

[0070] PETG uses Eastman's Eastar GN078.

[0071] Step (1): Add 10 parts PETG, 0.05 parts CHDM, and 0.35 parts stabilizer TPP to a high-speed mixer and stir at 500 r / min for 5 min. Then, use an extruder to melt-blend the mixture to obtain blend A with an intrinsic viscosity of 0.60 dL / g. Wherein: the high-speed mixer is added to the feed port of a single-screw extruder, and the temperatures of zones one, two, three, and four of the single-screw barrel are set to 220℃, 230℃, 240℃, and 240℃ respectively.

[0072] Step (2): Melt-state A and 7 parts of LOTADER AX8900 are melt-blended in a twin-screw side-feed extruder to obtain blend B. The melt-blending conditions are as follows: a twin-screw extruder is selected as the twin-screw side-feed extruder; LOTADER AX8900 is added at the first feed port; and molten state A is conveyed to the extruder through the melt section feed port. The temperatures of zones one through ten of the twin-screw barrel are set to 210℃, 215℃, 220℃, 225℃, 230℃, 235℃, 240℃, 240℃, 240℃, and 245℃, respectively.

[0073] Step (3): 82 parts PETG and 0.6 parts antioxidant 1222 were added to the first feed port of the twin-screw extruder. Blend B was then fed to the second feed port of the twin-screw extruder using a side feeder. The material was then extruded and pelletized. Standard test specimens were prepared using an injection molding machine. The melt temperature during both the blending extrusion and injection molding processes was maintained within the range of 200–250°C.

[0074] Example 5:

[0075] For PETG, Eastman's Eastar GN078 was selected, and for PBT, Yizheng Chemical Fiber's XW321 was selected.

[0076] Step (1): Add 10 parts PETG, 4 parts PBT, 0.05 parts CHDM, and 0.35 parts stabilizer TPP to a high-speed mixer and stir at 500 r / min for 5 min. Then, use an extruder to melt-blend the mixture to obtain blend A with an intrinsic viscosity of 0.61 dL / g. Wherein: The high-speed mixer is added to the feed port of a single-screw extruder, and the temperatures of zones one, two, three, and four of the single-screw barrel are set to 220℃, 230℃, 240℃, and 240℃ respectively.

[0077] Step (2): Melt-state A and 7 parts of LOTADER AX8900 are melt-blended in a twin-screw side-feed extruder to obtain blend B. The melt-blending conditions are as follows: a twin-screw extruder is selected as the twin-screw side-feed extruder; LOTADER AX8900 is added at the first feed port; and molten state A is conveyed to the extruder through the melt section feed port. The temperatures of zones one through ten of the twin-screw barrel are set to 210℃, 215℃, 220℃, 225℃, 230℃, 235℃, 240℃, 240℃, 240℃, and 245℃, respectively.

[0078] Step (3): 78 parts PETG and 0.6 parts antioxidant 1222 were added to the first feed port of the twin-screw extruder. Blend B was then fed to the second feed port of the twin-screw extruder using a side feeder. The material was then extruded and pelletized. Standard test specimens were prepared using an injection molding machine. The melt temperature during both the blending extrusion and injection molding processes was maintained within the range of 200–250°C.

[0079] Example 6:

[0080] PETG was selected from Eastman's Eastar GN078, and PBS was selected from Lanshan Tunhe Company's TH803S.

[0081] Step (1): Add 10 parts PETG, 4 parts PBST, 0.05 parts CHDM, and 0.35 parts stabilizer TPP to a high-speed mixer and stir at 500 r / min for 5 min. Then, use an extruder to melt-blend the mixture to obtain blend A with an intrinsic viscosity of 0.67 dL / g. Wherein: the high-speed mixer is added to the feed port of a single-screw extruder, and the temperatures of zones one, two, three, and four of the single-screw barrel are set to 220℃, 230℃, 240℃, and 240℃ respectively.

[0082] Step (2): Melt-state A and 7 parts of LOTADER AX8900 are melt-blended in a twin-screw side-feed extruder to obtain blend B. The melt-blending conditions are as follows: a twin-screw extruder is selected as the twin-screw side-feed extruder; LOTADER AX8900 is added at the first feed port; and molten state A is conveyed to the extruder through the melt section feed port. The temperatures of zones one through ten of the twin-screw barrel are set to 210℃, 215℃, 220℃, 225℃, 230℃, 235℃, 240℃, 240℃, 240℃, and 245℃, respectively.

[0083] Step (3): 78 parts PETG and 0.6 parts antioxidant 1222 were added to the first feed port of the twin-screw extruder. Blend B was then fed to the second feed port of the twin-screw extruder using a side feeder. The material was then extruded and pelletized. Standard test specimens were prepared using an injection molding machine. The melt temperature during both the blending extrusion and injection molding processes was maintained within the range of 200–250°C.

[0084] Example 7:

[0085] For PETG, Eastman's Eastar GN078 was selected, and for PBAT, Yizheng Chemical Fiber's TA200 was selected.

[0086] Step (1): Add 10 parts PETG, 4 parts PBAT, 0.05 parts CHDM, and 0.35 parts stabilizer TPP to a high-speed mixer and stir at 500 r / min for 5 min. Then, use an extruder to melt-blend the mixture to obtain blend A with an intrinsic viscosity of 0.66 dL / g. Wherein: the high-speed mixer is added to the feed port of a single-screw extruder, and the temperatures of zones one, two, three, and four of the single-screw barrel are set to 220℃, 230℃, 240℃, and 240℃ respectively.

[0087] Step (2): Melt-state A and 7 parts of LOTADER AX8900 are melt-blended in a twin-screw side-feed extruder to obtain blend B. The melt-blending conditions are as follows: a twin-screw extruder is selected as the twin-screw side-feed extruder; LOTADER AX8900 is added at the first feed port; and molten state A is conveyed to the extruder through the melt section feed port. The temperatures of zones one through ten of the twin-screw barrel are set to 210℃, 215℃, 220℃, 225℃, 230℃, 235℃, 240℃, 240℃, 240℃, and 245℃, respectively.

[0088] Step (3): 78 parts PETG and 0.6 parts antioxidant 1222 were added to the first feed port of the twin-screw extruder. Blend B was then fed to the second feed port of the twin-screw extruder using a side feeder. The material was then extruded and pelletized. Standard test specimens were prepared using an injection molding machine. The melt temperature during both the blending extrusion and injection molding processes was maintained within the range of 200–250°C.

[0089] Table 2 shows the test results of various material properties in Comparative Examples 3-4 and Examples 4-7:

[0090] A-terminal carboxyl group of the mixture (mol / t) / / 42 33 29 30 Hydroxyl group at terminal A of the mixture (mol / t) / / 106 98 90 94 Intrinsic viscosity of mixture A (dL / g) / / 0.60 0.61 0.67 0.66 Raw materials (parts) in the mixture 0 0 10 10 10 10 Toughening agent (parts) 7 15 7 7 7 7 Tensile strength (MPa) 48.3 40.6 49.3 50.2 51.3 52.3 Bending strength (MPa) 55.3 50.3 60.5 60.5 53.6 52.3 <![CDATA[Impact Strength (kJ / m 2 )]]> 13.5 55.8 53.3 56.2 65.3 68.8

[0091] Compared with Comparative Example 3 using conventional processes, the high-toughness polyester composition prepared by the unique blending process of this invention exhibits 3-4 times higher impact strength without affecting the material's mechanical strength. Compared with Comparative Example 4 using high amounts of additives, the high-toughness polyester composition prepared by the unique blending process of this invention shows significant advantages in mechanical properties and also improves impact performance. Therefore, the polyester composition prepared by this invention possesses excellent impact resistance, a simple production process, low cost, and broad application prospects.

Claims

1. A method for preparing a high-toughness polyester composition, characterized in that: The method includes the following steps: A portion of the polyester was melt-blended with additive I to obtain blend A; In step (1), the additive I mentioned in step (1) is selected from water and antioxidant in a mass ratio of 1:20~40; or the additive I is selected from terephthalic acid ester polymer, diol and heat stabilizer in a mass ratio of 70~90:1:5~10; or the additive I is selected from diol and heat stabilizer in a mass ratio of 1:5~10. The polyester is selected from polyethylene terephthalate 1,4-cyclohexanediol ester; (2) Blend A is obtained by melt blending the blend A with the toughening agent; the toughening agent is KRATONFG1924 or LOTADER® AX8900; (3) The remaining polyester, additive II and blend B are melt-blended, and the mixture is finally extruded and pelletized or made into other suitable shapes; Additive II is selected from chain extenders, colorants, release agents, antioxidants, flame retardants, and any combination thereof; The weight parts of polyester, additive I, toughening agent and additive II are 75~95 parts, 0.1~5 parts, 5~20 parts and 0.1~2 parts, respectively.

2. The method for preparing the high-toughness polyester composition according to claim 1, characterized in that: The intrinsic viscosity of blend A in step (1) is 0.57~0.67 dL / g, the total amount of terminal carboxyl groups and terminal hydroxyl groups is 120~180 mol / t, and the molar ratio of terminal carboxyl groups and terminal hydroxyl groups is 1:6~1:

2.

3. The method for preparing the high-toughness polyester composition according to claim 1, characterized in that: A portion of the polyester is 5-30 wt% of the total polyester content.

4. The method for preparing the high-toughness polyester composition according to claim 3, characterized in that: A portion of the polyester is 5-20 wt% of the total polyester content.

5. The method for preparing the high-toughness polyester composition according to claim 1, characterized in that: The blend A is in a solid or molten state.

6. The method for preparing the high-toughness polyester composition according to claim 5, characterized in that: The blend A is in a molten state.

7. The method for preparing the high-toughness polyester composition according to claim 1, characterized in that: The diol mentioned in step (1) is selected from at least one of ethylene glycol, propylene glycol, butanediol, hexanediol, 1,4-cyclohexanediol, isosorbide, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; The terephthalate polymer mentioned in step (1) is selected from at least one of PBT, PBS, PBAT and PBST; The antioxidant is selected from at least one of antioxidant 1010, antioxidant 1076 and antioxidant 1222; The heat stabilizer is selected from at least one of trimethyl phosphate (TMP), triethyl phosphate (TEP), triethyl phosphate (TEPA), and triphenyl phosphate (TPP).

8. The method for preparing the high-toughness polyester composition according to claim 7, characterized in that: The diol mentioned in step (1) is 1,4-cyclohexanediethanol.

9. The method for preparing the high-toughness polyester composition according to claim 1, characterized in that: The melt blending process uses a melt mixer selected from one of a single-screw or twin-screw extruder, a mixer, a kneader, an internal mixer, or an injection molding machine; the temperature of the melt mixer is 180~260℃.

10. The method for preparing the high-toughness polyester composition according to claim 9, characterized in that: The temperature of the melt mixer is 200~250℃.

11. The method for preparing the high-toughness polyester composition according to claim 7, characterized in that: Additive II is antioxidant 1222 or antioxidant 1010.

12. A high-toughness polyester composition, characterized in that: The composition is prepared by the method according to any one of claims 1-11.

13. The application of the high-toughness polyester composition obtained by the method of claim 1 in cosmetic packaging, food utensils, household goods, medical devices, machinery and equipment, indoor and outdoor signage, and furniture and building materials.

Citation Information

Patent Citations

  • High heat-resistant fire-retardant reinforced polyethylene terephthalate (PET) composition and preparation method thereof

    CN102816414B

  • A thermoplastic polyester composition and a method for preparing the same

    CN103131138B

  • Method for preparing high-toughness PET (Polyethylene Terephthalate)

    CN105524433A

  • High-elongation spraying PC / PBT alloy material and preparation method thereof

    CN112341781A

  • Toughened polyethylene terephthalate glycol (PETG) material and preparation method thereof

    CN102399422A